SURVIVAL, INDUCTION AND RESUSCITATION OF Vibrio cholerae FROM THE VIABLE BUT NON-CULTURABLE STATE IN THE SOUTHERN CARIBBEAN SEA - Fernández-Delgado, Milagro; García-Amado, María Alexandra; Contreras, Monica; Incani, Renzo Nino; Chirinos, Humberto; Rojas, Héctor; Suárez, Paula (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
The causative agent of cholera, Vibrio cholerae, can enter into a viable but non-culturable (VBNC) state in response to unfavorable conditions. The aim of this study was to evaluate the in situ survival of V. cholerae in an aquatic environment of the Southern Caribbean Sea, and its induction and resuscitation from the VBNC state. V. cholerae non-O1, non-O139 was inoculated into diffusion chambers placed at the Cuare Wildlife Refuge, Venezuela, and monitored for plate, total and viable cells counts. At 119 days of exposure to the environment, the colony count was < 10 CFU/mL and a portion of the bacterial population entered the VBNC state. Additionally, the viability decreased two orders of magnitude and morphological changes occurred from rod to coccoid cells. Among the aquatic environmental variables, the salinity had negative correlation with the colony counts in the dry season. Resuscitation studies showed significant recovery of cell cultivability with spent media addition (p < 0.05). These results suggest that V. cholerae can persist in the VBNC state in this Caribbean environment and revert to a cultivable form under favorable conditions. The VBNC state might represent a critical step in cholera transmission in susceptible areas.